2008
DOI: 10.1007/s10072-008-0908-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary headache and multiple sclerosis: preliminary results of a prospective study

Abstract: The aim of this study was to explore the association between different types of headache (HA) and the clinical features of multiple sclerosis (MS). The relationship between HA and MS-specific therapies was also analysed. A total of 102 MS patients were recruited at the MS Centre of S. Andrea Hospital in Rome. According to International Headache Society criteria, the lifetime prevalence of primary HA was 61.8%. Migraine was observed more often in young relapsing-remitting MS patients, whilst tension-type HA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 10 publications
5
36
1
5
Order By: Relevance
“…In another prospective study with no control group, Villani et al reported that the life-long prevalence of primary headaches in 102 patients with MS was 61.8% (12). In yet another prospective study without a control group undertaken by Boneschi et al, the life-long prevalence of headache was found to be 35.5% in 428 patients with MS (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another prospective study with no control group, Villani et al reported that the life-long prevalence of primary headaches in 102 patients with MS was 61.8% (12). In yet another prospective study without a control group undertaken by Boneschi et al, the life-long prevalence of headache was found to be 35.5% in 428 patients with MS (24).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although some studies showed that RRMS could be correlated with migraines, this issue could not be confirmed with other studies (3)(4)(5)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). In another study, it was suggested that deregulation of the serotonergic system may also be involved in the pathogenesis of MS as well as migraines (13).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Relapsing remitting MS (RRMS)'de baş ağrısının, ilk MS semptomları ile be-raber başlayabildiğine, baş ağrısının ataklar döneminde rekürrens göstere-bildiğine dair çalışmalar mevcuttur (3-5, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Bir başka makalede atak sıra-sında migreni olan 3 olgu sunumundan hareketle, MS'in patogenezinde de migrende olduğu gibi serotenerjik sistemin disregülasyonunun yer alabileceği ileri sürülmüştür (13).…”
unclassified
“…Headaches are not integrated, although since 2000, almost every study about headache in MS showed a high prevalence of up to 78% [5][6][7][8]. A possible reason could be that headaches are considered a coincident disease and not a symptom of MS.…”
Section: Introductionmentioning
confidence: 99%